Analisis Kadar Gula Reduksi pada Fermentasi Kacang Gude (Cajanus cajan) oleh Aspergillus niger - Pujiati, Pujiati; Primiani, C. Novi (Universitas Sebelas Maret, 2016)
Pigeonpea (Cajanus cajan) is a tropical legume grown mainly in Indonesia. Though largely considered an orphan crop, pigeonpea has a huge untapped potential for improvement both in quantity and quality of yield. Pigeonpea seeds contain 65 % starch. Based on its starch level can be use as substrate of solid-state fermentation. Solid-state fermentation using Aspergillus niger because they have amylolytic and cellulolytic activity and not produce micotoxin. This study was carried out to know the change reducing sugar level of fermenting pigeonpea as to know a success of fermentation process. Completely randomized design was used, data result were analyzed with ANOVA, then were continued with Least Significant Difference. Different parameters such as inoculums concentration and incubation time. Inoculum concentration of 2 mL/g and incubation time of 72 hours give the best result of 12,50%.Keywords: solid state fermentation, glucose reduction, proteolitic, pigeon pea